Natural Toxins: Environmental Fate and Safe Water Supply Conference Abstract Book and Proceedings. 24 th-25th September 2020 - Bruun Hansen, Hans; Hilscherová, Klára (Masaryk University Press, 2020)
Plants, bacteria, cyanobacteria, algae and other organisms produce a vast diversity of bioactive and toxic natural compounds. We know that many of these toxins are mobile and can be produced in high amounts close to or within drinking water reservoirs. Natural toxins represent emerging classes of environmental contaminants for which we have very limited insight on occurrence, fate and effects. The konference "Natural toxins: Environmental Fate and Safe Water Supply" addresses knowledge gaps within the field of natural toxins, target, non-target, suspect and effect-directed analysis, distribution, fate, toxicity and management of natural toxins in aquatic environments and drinking water reservoirs. These proceedings are a collection of the abstracts to contributions presented at the conference.